Factors Associated with Nursing Code of Ethics Practice in Gurage Zone, SNNPR, Ethiopia, 2022 - Haile TG (Dove Medical Press, 2022)
Tariku Gebre Haile Department of Nursing, College of Medicine and Health Sciences, Wolkite University, Wolkite, EthiopiaCorrespondence: Tariku Gebre Haile, Tel +251 917411183, Email tareser23@gmail.comIntroduction: Ethical codes are a set of systematic binding and guiding rules defining morally acceptable ethical behavior. The nursing profession is the backbone of the medical industry and the front-line healthcare service providers. Nowadays providing ethically competent, compassionate and respectful care is highly essential.Objective: Determining Factors associated with nursing code ethics practice among nurses working in Gurage zone hospitals, 2022.Methods: From February 1 to March 30, 2022, an institution-based cross-sectional study using the non-probability convenient sampling method was used to choose the study participants. Pretested self-administered questionnaires were used to collect data and entered using Epi info 3.5.1 versions, then exported to SPSS version 23 for analysis. Bivariate and multivariable logistic regression analyses were employed to identify associated factors. Variables having a P-value of < 0.05 in the multivariable logistic regression model were considered as significantly associated variables.Results: This study was completed through 413 study participants with 97.86% response rate. Fifty-three percent of nurse practitioners were found to adhere to the nursing code of ethics. Sex [females] (AOR [95% CI] 3.69 (2.14- 6.36)), working ward [surgical ward] (AOR[95% CI] 4.84(1.94- 12.06)) and [pediatrics ward] (AOR[95% CI] 0.36(0.17- 0.77)), Years of working experience [5- 10 years] (AOR[95% CI] 2.08 (1.13- 3.84)) and work experience [> 10 years] (AOR [95% CI] 3.49 (1.798- 6.76)), nurses who had training (AOR[95% CI] 5.02(2.85- 8.83)) and nurses who had frequent supportive supervision system (AOR[95% CI] 2.27(1.29- 3.98)) were factors that associated with nursing code of ethics practice.Conclusion: In this study, over half of the nurses practiced the nursing code of ethics in a professional manner. Nursing code of ethics practice was substantially correlated with factors, sex, working ward, years of experience, training, and regular supportive supervision. Therefore, it is strongly advised that all parties involved implement a regular supporting supervision system and give up-to-date training to staff nurses.Keywords: code of ethics, practice, knowledge, attitude